Star course : nineteenth-century lecture tours and the consolidation of modern celebrity - Cherches, Peter (Transdisciplinary studies, 2017)
In the quarter century following the Civil War, "star courses" brought people famous for diverse pursuits before American audiences as lecturers, transforming what had been a largely educational institution into a major form of mainstream popular entertainment. No longer reliant on a rhetoric of uplift that had characterized the more sedate antebellum American lyceum movement exemplified by Ralph Waldo Emerson, Gilded-Age lecture series presented a wider range of individuals--writers, humorists, preachers, actors, scientists, and political activists--to an American public yearning to see and hear the famous and the infamous of all stripes in the flesh. Borrowing the word "star" from the theater, these national lecture tours helped to solidify an already evolving notion of celebrity through emerging public relations techniques and an expanding transportation network that transformed the lecture platform into a pre-electronic form of mass media, prefiguring much of the content of television and radio. Among the lecturers discussed are Mark Twain, the superstar cleric Henry Ward Beecher, cartoonist Thomas Nast, and African explorer Henry Morton Stanley, as well as the 19th wife of Brigham Young. Based on extensive archival research and newspaper accounts of the time, Star Course recaptures a lost chapter in American popular performance history. "In the century before television brought stars into our living rooms, celebrities crisscrossed the nation, bringing entertainment and perspectives to towns large and small. Peter Cherches, through his careful research and engaging prose, brings the stars and impresarios of the nineteenth-century lecture circuit back from the dead and gives us a front-row seat. This is an important book."--David T.Z. Mindich, author of Just the Facts: How "Objectivity" Came to Define American Journalism and chair of Temple University's journalism department